Buparlisib and paclitaxel in patients with platinum-pretreated recurrent or metastatic squamous cell carcinoma of the head and neck (BERIL-1): a randomised, double-blind, placebo-controlled phase 2 trial. Issue 3 (March 2017) - Soulières, Denis; Faivre, Sandrine; Mesía, Ricard; Remenár, Éva; Li, Shau-Hsuan; Karpenko, Andrey; Dechaphunkul, Arunee; Ochsenreither, Sebastian; Kiss, Laura Anna; Lin, Jin-Ching; Nagarkar, Raj; Tamás, László; et al.
Summary: Background: Phosphatidylinositol 3-kinase (PI3K) pathway activation in squamous cell carcinoma of the head and neck contributes to treatment resistance and disease progression. Buparlisib, a pan-PI3K inhibitor, has shown preclinical antitumour activity and objective responses in patients with epithelial malignancies. We assessed whether the addition of buparlisib to paclitaxel improves clinical outcomes compared with paclitaxel and placebo in patients with recurrent or metastatic squamous cell carcinoma of the head and neck. Methods: In this multicentre, randomised, double-blind, placebo-controlled phase 2 study (BERIL-1), we recruited patients aged 18 years and older with histologically or cytologically confirmed recurrent and metastatic squamous cell carcinoma of the head and neck after disease progression on or after one previous platinum-based chemotherapy regimen in the metastatic setting. Eligible patients were enrolled from 58 centres across 18 countries and randomly assigned (1:1) to receive second-line oral buparlisib (100 mg once daily) or placebo, plus intravenous paclitaxel (80 mg/m 2 on days 1, 8, 15, and 22) in 28 day treatment cycles. Randomisation was done via a central patient screening and randomisation system with an interactive (voice and web) response system and stratification by number of previous lines of therapy in the recurrent and metastatic setting and study site. Patients and investigators (including local radiologists) were masked to treatment assignment from randomisation until the final overall survival analysis. The primary endpoint was progression-free survival by local investigator assessment per Response Evaluation Criteria In Solid Tumors (version 1.1) in all randomly assigned patients. Efficacy analyses were done on the intention-to-treat population, whereas safety was analysed in all patients who received at least one dose of study drug and had at least one post-baseline safety assessment according to the treatment they received. This trial is registered with ClinicalTrials.gov, number NCT01852292, and is ongoing but no longer enrolling patients. Findings: Between Nov 5, 2013, and May 5, 2015, 158 patients were enrolled and randomly assigned to receive either buparlisib plus paclitaxel (n=79) or placebo plus paclitaxel (n=79). Median progression-free survival was 4·6 months (95% CI 3·5–5·3) in the buparlisib group and 3·5 months (2·2–3·7) in the placebo group (hazard ratio 0·65 [95% CI 0·45–0·95], nominal one-sided p=0·011). Grade 3–4 adverse events were reported in 62 (82%) of 76 patients in the buparlisib group and 56 (72%) of 78 patients in the placebo group. The most common grade 3–4 adverse events (occurring in ≥10% of patients in the buparlisib group vs the placebo group) were hyperglycaemia (17 [22%] of 76 vs two [3%] of 78), anaemia (14 [18%] vs nine [12%]), neutropenia (13 [17%] vs four [5%]), and fatigue (six [8%] vs eight [10%]). Serious adverse events (regardless of relation to study treatment) were reported for 43 (57%) of 76 patients in the buparlisib group and 37 (47%) of 78 in the placebo group. On-treatment deaths occurred in 15 (20%) of 76 patients in the buparlisib group and 17 (22%) of 78 patients in the placebo group; most were caused by disease progression and none were judged to be related to study treatment. Interpretation: On the basis of the improved clinical efficacy with a manageable safety profile, the results of this randomised phase 2 study suggest that buparlisib in combination with paclitaxel could be an effective second-line treatment for patients with platinum-pretreated recurrent or metastatic squamous cell carcinoma of the head and neck. Further phase 3 studies are warranted to confirm this phase 2 finding. Funding: Novartis Pharmaceuticals Corporation.